Enhanced magnetic flux density mapping using coherent steady state equilibrium signal in MREIT - Woo Chul Jeong; Mun Bae Lee; Saurav Z. K. Sajib; Hyung Joong Kim; Oh In Kwon; Eung Je Woo (AIP Advances, 2016)
Measuring the z-component of magnetic flux density B = (Bx, By, Bz) induced by transversally injected current, magnetic resonance electrical impedance tomography (MREIT) aims to visualize electrical property (current density and/or conductivity distribution) in a three-dimensional imaging object. For practical implementations of MREIT technique, it is critical to reduce injection of current pulse within safety requirements. With the goal of minimizing the noise level in measured Bz data, we propose a new method to enhance the measure Bz data using steady-state coherent gradient multi-echo (SSC-GME) MR pulse sequence combining with injection current nonlinear encoding (ICNE) method in MREIT, where the ICNE technique injects current during a readout gradient to maximize the signal intensity of phase signal including Bz. The total phase offset in SSC-GME includes additional magnetic flux density due to the injected current, which is different from the phase signal for the conventional spoiled MR pulse sequence. We decompose the magnetization precession phase from the total phase offset including Bz and optimize Bz data using the steady-state equilibrium signal. Results from a real phantom experiment including different kinds of anomalies demonstrated that the proposed method enhanced Bz comparing to a conventional spoiled pulse sequence.